Pengaruh Elemen Lanskap Taman Kota Bogor pada Psiko-Fisiologi, Visual Behavior, dan Persepsi dengan Metode Eye-Tracking - Pamungkas, Aditya Aji; Pratiwi, Prita Indah; Sulistyantara, Bambang (Jurnal Lanskap Indonesia, 2025)
Rapidly growing urbanization results in reduced access to the natural environment, as well as the quantity and quality of urban green spaces (UGS). The area of UGS in Bogor City in 2021 has only reached 4.2%, while the public UGS that is well managed in 2020 is around 75% of the total. Information on people's perceptions and preference studies serves as an important input for UGS planning and management. Psychological methods, including eye-tracking, can provide a comprehensive way to improve understanding of human perception of landscapes. This study aimed to analyze the effect of landscape on psycho-physiology, analyze visual behaviour within different types of landscapes, analyze the evaluation index of urban park landscapes, and obtain recommendations regarding landscape elements. The results of the study showed that observing landscape photos had a significant effect on respondents' psychology and physiological attributes (p<0.05), but was not significant on blood oxygen saturation (p=0.88). Eye tracking indicators showed that tree has the highest fixation count and fixation duration, with the lowest time to first fixation. Respondents' visual behaviour mainly focused on the center point of the photo, vanishing point, dominant objects such as location signs, and randomly on points of interest in the photo. The landscape evaluation index positively correlated with the percentage of greenery. The findings recommend a minimum threshold of greenery for urban parks consisting of a proportion of 22% trees, 14% shrubs, and 12% lawns as a critical point for user perception and preference.